2022
DOI: 10.3389/fpls.2022.941231
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of genes related to alkaloid biosynthesis and the regulation mechanism under precursor and methyl jasmonate treatment in Dendrobium officinale

Abstract: Dendrobium officinale is both a traditional herbal medicine and a plant of high ornamental and medicinal value. Alkaloids, especially terpenoid indole alkaloids (TIAs), with pharmacological activities are present in the tissues of D. officinale. A number of genes involved in alkaloid biosynthetic pathways have been identified. However, the regulatory mechanisms underlying the precursor and methyl jasmonate (MeJA)-induced accumulation of alkaloids in D. officinale are poorly understood. In this study, we collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…The MYB gene family is widely involved in plant growth and development, not only in model plants, but also in major crops and horticultural plants [ 85 88 ]. Studies on MYB in D. officinale mainly focused on polysaccharide synthesis [ 89 ], flower development [ 89 ], stress response [ 90 , 91 ], alkaloid biosynthesis [ 92 ] and terpenoid biosynthesis [ 93 ], suggesting that DoDELLA1 and DoMYBs may co-regulate one or more aspects of D. officinale , although the related functions need to be further explored and verified. WALLS ARE THIN1 (WAT1) is a plant-specific protein that regulates the secondary cell wall thickness of stem fibers and participates in the integration of auxin signaling in A. thaliana fibers [ 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MYB gene family is widely involved in plant growth and development, not only in model plants, but also in major crops and horticultural plants [ 85 88 ]. Studies on MYB in D. officinale mainly focused on polysaccharide synthesis [ 89 ], flower development [ 89 ], stress response [ 90 , 91 ], alkaloid biosynthesis [ 92 ] and terpenoid biosynthesis [ 93 ], suggesting that DoDELLA1 and DoMYBs may co-regulate one or more aspects of D. officinale , although the related functions need to be further explored and verified. WALLS ARE THIN1 (WAT1) is a plant-specific protein that regulates the secondary cell wall thickness of stem fibers and participates in the integration of auxin signaling in A. thaliana fibers [ 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further clarify the roles of the WRKY genes in abiotic stress, we conducted a comparative transcriptomic analysis of MeJA-treated D. officinale at different stages ( Jiao et al, 2022 ). The results showed that WRKY family members were differentially expressed at different treatment times and showed two expression patterns ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…HPLC showed that the activity of strictosidine synthase was improved, and carapanaubine (a type of TIA) levels were significantly up-regulated. 29 In addition, total alkaloid content in the D. of f icinale protocorms treated with TIA precursor substances (tryptophan and saponin) and MeJA for 4 h was significantly higher than that in the untreated group. Further transcriptome analysis revealed that alkaloid content was highly correlated with the expression of six genes involved in alkaloid biosynthesis, including DHS (Dca021396), DoADH (Dca025688), DoTYDC (Dca021379), and DoTR (Dca000522, Dca027425, and Dca000521), as well as seven genes related to jasmonate biosynthesis, including DoLOX (Dca023278), DoAOS (Dca022684), and DoOPR (newGene_9791, newGene_13686, Dca023268, Dca001807, and Dca000910), which may play important roles in the alkaloid biosynthesis of D. of f icinale.…”
Section: Alkaloidsmentioning
confidence: 85%
“…30 Another study 31 suggested that the alkaloid content in D. off icinale samples treated with MeJA was highest at 32 days (343 μg/g), consistent with previous studies. 29 Furthermore, based on solid-phase extraction coupled with high-performance liquid chromatographytandem mass spectrometry (SPE-HPLC-LC-MS/MS), 49 compounds were identified from the MeJA-treated samples, including seven alkaloids. 31 Despite the identification of many genes related to alkaloid synthesis through multiomics analysis, most genes have not yet been confirmed by functional studies, and their mechanisms remain incompletely understood.…”
Section: Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation